Staying connected and navigating the pandemic: A mixed-methods study into the impact of COVID-19 on UK Veterans - Brooks, Dan (2021)
Background: The 2019 coronavirus pandemic has posed a challenge to society to cope with an unprecedented threat. Veterans with pre-existing mental health conditions, such as PTSD, may be susceptible to further re-traumatisation due to COVID-19 restrictions and increased anxiety and depression. Bonding and a sense of connectedness with others are seen as basic psychological needs for maintaining wellbeing. Decreased social connectedness can play a significant role in creating barriers to coping and worsening psychological problems. As the pandemic progresses, the current UK restrictions may challenge veterans’ ability to function, and their abilities to cope, stay connected and adapt.